Assessing body condition scores, weight gain dynamics, and fecal egg counts in feedlot and non-feedlot cattle within high throughput abattoirs of the Eastern Cape Province - Mpofu, Beautiful Isabel; Slayi, Mhlangabezi; Mutero, Gabriel; Mlahlwa, Sisipho; Jaja, Ishmael Festus (Frontiers in Animal Science, 2023)
Feedlots have emerged as an ideal mitigation option to pursue sustainable and efficient livestock production. This paper aims to elucidate how the establishment and widespread adoption of feedlots have provided solutions to complex problems of food security, animal welfare, and environmental sustainability. An observational cross-sectional study compared fecal egg count per gram (EPG), weight gain, and body condition score (BCS) in feedlot and non-feedlot cattle at high throughput abattoirs. Cattle (n = 120) of different age and sex groups, farms, and breeds were selected from two commercial abattoirs (EA1 and EA2) in the Eastern Cape Province. At EA1, non-feedlot cattle exhibited higher EPG values (323.3±28.9) than feedlot cattle (73.3±13.3), indicating a potentially greater susceptibility to internal parasitic infections. The similar weight gains between feedlot (298.1±4.7) and non-feedlot cattle (287.16±7.79) were attributed to the sufficient natural pasture in the communally raised cattle. However, body condition scores were significantly (P< 0.05) better in feedlot than in non-feedlot cattle. Nonetheless, the feedlot farms of origin had a significant effect (P< This is a provisional file, not the final typeset article 0.05) on the EPG and body condition score values in EA1, with no significant effect in EA2. Moreover, the negative correlation between EPG and body condition scores highlights that as parasite load increases, there might be a subtle tendency for body condition to decrease. These results underscore the importance of feedlots as an effective management strategy to improve animal health and productivity. Further investigations into the factors driving the differences in non-feedlot cattle are needed for informed decision-making in livestock management and abattoir operations.